Treating opioid addiction with opioids: groundbreaking science or absolute chaos? - H. F. M’Guil; Melanie Khanchana Amarasekera (Military Medicine, 2026)
As the opioid crisis continues to impact communities, developing an effective treatment for opioid addiction is a critical public health challenge. This study aims to explore the use of opioid agonists for the treatment of opioid addiction and examine potential controversies surrounding it. T rea tm e nt of O U D with medication such as Methadone and Buprenorphine has been proven to be effective in the treatment of overdose of opioids. The mechanism of action for these opioid agonists are primarily focused on maintenance of the opioid addiction and detoxification. In the United States Buprenorphine is used for office based treatment, whereas Methadone is provided only in the Opioid usage overdose treatment facility centers. H o w e v er, many s tatistical analyses found that opioid agonist treatment for OUD, can pose a major risk for the public health and safety, potentially causing more harm to the patient than the OUD itself. It is crucial to address the issues of misuse and stigma of medication associated with medication assisted treatment in order to optimize patient care of individuals with OUD.